Legal Aspects of Family Constitution in the Process of Transfer of a Family Business - Taneski, Ana; Koritnik, Boštjan (Izzivi prenosa vodenja na naslednjo generacijo v družinskem podjetju, 2025)
This chapter addresses the legal aspect of family business succession planning, focusing on the institution of the family constitution. It first analyzes the legal specificities of family businesses and then defines the role and significance of the family constitution. The aim is to examine how a family constitution can support successful business transfer and strengthen family relations, which are vital for long-term cooperation. The research includes an interview with Domen Deu, the intended successor of the Slovenian company Dines d.o.o., where only an informal succession agreement currently exists. Family members act as both owners and managers but are unfamiliar with the family constitution, and thus it has not been implemented. Although this has not hindered operations so far, formalizing agreements in a family constitution could stabilize relationships, align processes between family, ownership, and business, and help prevent internal conflicts. Such an approach could positively influence the company’s long-term stability, market performance, and overall business results.